Gas Exchange Disturbances Regulate Alveolar Fluid Clearance during Acute Lung Injury - Vadász, István; Sznajder, Jacob I. (Frontiers in Immunology, 2017)
Disruption of the alveolar-capillary barrier and accumulation of pulmonary edema, if not resolved, result in poor alveolar gas exchange leading to hypoxia and hypercapnia, which are hallmarks of acute lung injury and the acute respiratory distress syndrome (ARDS). Alveolar fluid clearance (AFC) is a major function of the alveolar epithelium and is mediated by the concerted action of apically-located Na+ channels (ENaC) and the basolateral Na,K-ATPase driving vectorial Na+ transport. Importantly, those patients with ARDS who cannot clear alveolar edema efficiently have worse outcomes. While hypoxia can be improved in most cases by O2 supplementation and mechanical ventilation, the use of lung protective ventilation settings can lead to further CO2 retention. Whether the increase in CO2 concentrations has deleterious or beneficial effects has been a topic of significant controversy. Of note, both low O2 and elevated CO2 levels are sensed by the alveolar epithelium and by distinct and specific molecular mechanisms impair the function of the Na,K-ATPase and ENaC thereby inhibiting AFC and leading to persistence of alveolar edema. This review discusses recent discoveries on the sensing and signaling events initiated by hypoxia and hypercapnia and the relevance of these results in identification of potential novel therapeutic targets in the treatment of ARDS.